Research on stimulating the activity of the iron tailings by alkali fusion. (November 2015) - Peng, L.; Jiao, B. Q.; Xu, G. J.; Huang, X.
Abstract : The characteristics of iron ore used in this paper were investigated by using X-ray fluorescence and X-ray diffraction; the main mineral structures of iron ore tailings are chlorite and feldspar. The iron ore tailings, which are high alumina samples, can be used as a gelling material. Alkali fusion was used to activate the iron ore tailings. Characterisation of alumina activity was shown by inductively coupled plasma optical emission spectrometer. The experiments show that thermal activation alone cannot improve the activity of iron ore tailings, but alkali fusion approach can significantly improve the activity of the iron ore tailings alumina. In the orthogonal experiment, the inputs of NaOH to improve the iron ore tailings alumina activity were significant, but temperature (60 minutes) and time (350°C) were less significant, taking into account economic, environmental, safety and other issues The results of single-factor experiments showed that when the amount of NaOH was 110%, iron tailings activity reached maximum. Alkali fusion was used to improve the activity of iron ore tailings alumina experiments, the optimal combination of temperature, time, NaOH inputs were selected: 350°C, 60 minutes, 110%.